2019
DOI: 10.1186/s12940-019-0509-z
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone levels associate with exposure to polychlorinated biphenyls and polybrominated biphenyls in adults exposed as children

Abstract: Background Michigan residents were directly exposed to endocrine-disrupting compounds, polybrominated biphenyl (PBB) and polychlorinated biphenyl (PCB). A growing body of evidence suggests that exposure to certain endocrine-disrupting compounds may affect thyroid function, especially in people exposed as children, but there are conflicting observations. In this study, we extend previous work by examining age of exposure’s effect on the relationship between PBB exposure and thyroid function in a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 71 publications
0
20
0
1
Order By: Relevance
“…Some studies have not observed the effect of PCBs on TSH [ 339 , 340 , 341 , 342 , 343 , 344 , 345 , 346 , 347 , 348 , 349 ] and thyroid hormone levels [ 339 , 340 , 341 , 348 , 350 ]. However, other studies have shown an increase [ 351 ] and a decrease [ 352 , 353 ] in TSH, an increase [ 347 , 353 ] and a decrease [ 344 , 346 , 351 , 352 , 354 ] in T3 and an increase [ 342 , 347 , 349 , 353 ] and a decrease [ 343 , 346 , 351 , 352 , 354 , 355 , 356 ] in T4 after exposure to PCBs. Although previous studies have investigated the effect of PBBs on the development of thyroid diseases [ 357 , 358 ], we have found only one study investigating the effect of PBBs on TSH and thyroid hormone levels in euthyroid individuals [ 349 ].…”
Section: Environmental Factors That Influence Tsh and Thyroid Hormone Levelsmentioning
confidence: 99%
“…Some studies have not observed the effect of PCBs on TSH [ 339 , 340 , 341 , 342 , 343 , 344 , 345 , 346 , 347 , 348 , 349 ] and thyroid hormone levels [ 339 , 340 , 341 , 348 , 350 ]. However, other studies have shown an increase [ 351 ] and a decrease [ 352 , 353 ] in TSH, an increase [ 347 , 353 ] and a decrease [ 344 , 346 , 351 , 352 , 354 ] in T3 and an increase [ 342 , 347 , 349 , 353 ] and a decrease [ 343 , 346 , 351 , 352 , 354 , 355 , 356 ] in T4 after exposure to PCBs. Although previous studies have investigated the effect of PBBs on the development of thyroid diseases [ 357 , 358 ], we have found only one study investigating the effect of PBBs on TSH and thyroid hormone levels in euthyroid individuals [ 349 ].…”
Section: Environmental Factors That Influence Tsh and Thyroid Hormone Levelsmentioning
confidence: 99%
“…The value for any congener below the LOD in a sample was imputed as the LOD divided by the square root of 2 45 . Previous studies in this population have reported high correlation between PBB congeners, high correlation between PCB congeners, and low correlation between PBB and PCB congeners 46 . The congeners were summed by wet-weight concentrations to give total PCB and total PBB values per person (total PCB = PCB-118+ PCB-138+ PCB-153+ PCB-180; total PBB = PBB-77+ PBB-101+ PBB-153+ PBB-180).…”
Section: Methodsmentioning
confidence: 47%
“…We did not have lifetime PCB data as our exposure variable was only measured in all participants www.nature.com/scientificreports www.nature.com/scientificreports/ at the same time as the administration of the health questionnaire 7,46 . Also, the age when first exposed to EDC has been shown to be important for the development of health outcomes 3,11,30,46,53 . However, due to the small number of people exposed in utero in this study, this was not able to be analyzed at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Quite a bit is known about interactions between age and environmental factors of endocrine disruption per se [ 38 40 ]. Many studies have found that earlier exposure in the perinatal period leads to the greatest alterations in behavior and physiology [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%